Fungicidas protectantes para el control de monilia (Moniliophthora roreri cif & par) en clones de cacao (Theobroma cacao l.) Eet-103 y ccn-51 - Franco Dominguez, Cristhian Jonathan (2016)
This project was conducted in the Experimental Farm "La Represa" property of the State Technical University of Quevedo, located on the premises Faita, Kilometer 7.5 of Via San Carlos, in the Canton Quevedo, Los Rios province, had a duration of July 1 to September 24 this year, entitled "protectant fungicides MONILIA CONTROL (Moniliophthora roreri Cif & Par) IN CLONES OF COCOA (Theobroma cacao L.) EET-103 and CCN-51" general purpose It was: To evaluate the use of protective fungicides for control of brown rot (Moniliophthora roreri Cif & Par) in clones of cacao (Theobroma cacao L) EET-103 and CCN-51 design was applied completely random (DCA) factorial arrangement x 4 (protectant fungicides) + 1 control (without fungicide) x 2 (clones of cacao), to determine the difference between treatment means to study the Tukey test (p <0.05) was used and the SAS statistical program was used. The most representative results showed the fungicide Mancozeb the NFP reference variable with an average of 7.58 small fruits, to the NMS, PFS, MNEM, Rend NCHW and variables. Kg ha-1 fungicide chlorothalonil showed their superiority on average 8.25; 1.1393; 10.67; 13.22 and 501.27 kg ha-1 respectively. Achieving higher productivity clone CCN-51 in all treatments. Chlorothalonil - CCN51 showed elevated superiority regarding the B / C is concluded emphasizing the properties of the fungicide chlorothalonil, which showed the highest rates in the variables evaluated. Investigations are expected to continue investigating on the scope of fungicides Protectants